Field notes contributed by Rene Laubach, winter 1982-1983 - Laubach, Reneet al (1982)
Winter report of birds and locations contributed by Rene Laubach. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1982-1983. Epson - sheet feed